Effect of FS-SMAT on microstructure and mechanical property of pure magnesium and AZ31 magnesium alloy - Long-Hai Hu; Jin-Hua Peng; Xiao-Xin Hu; Liang-Yu Chen; Maksym-M. Bobrov; Sheng Lu (Heat Treatment and Surface Engineering, 2023)
ABSTRACTA novel material processing method, friction stir-surface mechanical attrition treatment (FS-SMAT) was conducted on pure magnesium plate and AZ31 magnesium alloy plate. Two types of stir tools, spherical stir tool and plane stir tool, are designed to process FS-SMAT to reduce the heat input compared with the traditional friction stir processing (FSP). Microstructure evolution during FS-SMAT and its effect on mechanical property are investigated. FS-SMAT has different effect on microstructure and mechanical property when using the spherical and plane stir tools. Different heat input and plastic deformation can be produced due to the specific shapes of stir tools. Using a spherical stir tool, the grain size of pure magnesium plate was refined to 1.74 μm. The micro-hardness was improved from 40 HV to 63 HV. In contrast, after FS-SMAT with a plane stir tool, the grain size and micro-hardness of AZ31 magnesium alloy are 0.91 μm and 125 HV, respectively.